Antidiabetic properties of analog rice from local raw materials: a systematic review - Carolyn Lauwis; Cherilyn Theophila Maringka; Fiona Julieta; Paskalia Evangelista; Vincensius Marcellino; Elisabeth Rukmini (International Journal of Public Health Science (IJPHS), 2023)
Type 2 diabetes mellitus (T2DM) is a common disease, where about 90% of Indonesians suffer from high white rice consumption. According to various reports, analog rice from many raw materials has benefits for T2DM. This review aimed to identify nutritional content that can be found in various local raw materials for T2DM. In addition, this review explained the antidiabetic effects and mechanisms of the nutritional content. PRISMA guidelines were utilized as the basis of this systematic review. Relevant and related studies were determined by databases such as PubMed, Google Scholar, and Garuda. The identification process in those databases resulted in 284 articles, with only 56 articles included based on the final paper criteria. The primary keywords for the identification process include analog rice, T2DM, antidiabetic, glycemic index (GI), and fiber. Meanwhile, the secondary keywords are based on the review's local raw materials, such as purple yam, corn, banana, sorghum, and cassava. As a result, studies found nutritional compounds with antidiabetic properties inside analog rice made from different local raw materials. which each of them has different mechanisms to overcome T2DM. Therefore, the consumption of analog rice from purple yam, corn, banana, sorghum, and cassava has the potential to prevent T2DM.